Performance improvement of a switched reluctance machine with segmental rotors for hybrid electric vehicles. (July 2019) - Sun, Xiaodong; Diao, Kaikai; Yang, Zebin
Abstract: This paper investigates the performance improvement of a segmented-rotor switched reluctance machine (SSRM) with 16/10 stator/rotor poles. First, the application area, prototype and operation principle of the SSRM are introduced. Second, some important parameters are analyzed to get the optimal values. Then, the simulation results are proposed to show the improvement of the SSRM after optimization, and the improved fault-tolerant characteristic is presented by using finite element method (FEM). It is found that the SSRM after optimization can greatly improve the ability of fault-tolerant, reduce the torque ripple, and continuously operate when two phases of the SSRM have failure. Finally, the predicted static performance and the operation under the current chopper control system of the SSRM are verified by experiments.